2012
DOI: 10.1590/s1677-55382012000100008
|View full text |Cite
|
Sign up to set email alerts
|

When prone position is contraindicated or not preferable, can supine percutaneous nephrolithotomy solve the problem?

Abstract: ARTICLE INFO_______________________________________________________________ _____________________

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…This position allowed simultaneous antegrade and retrograde access to the urinary tract. After introduction of this position several other authors published studies [5] , [7] , [9] , [10] confirming the efficacy and safety of supine PCNL for treating most renal stones. The Barts flank-free modified supine position made further modifications allowing a wider field for percutaneous access [6] .…”
Section: Discussionmentioning
confidence: 92%
“…This position allowed simultaneous antegrade and retrograde access to the urinary tract. After introduction of this position several other authors published studies [5] , [7] , [9] , [10] confirming the efficacy and safety of supine PCNL for treating most renal stones. The Barts flank-free modified supine position made further modifications allowing a wider field for percutaneous access [6] .…”
Section: Discussionmentioning
confidence: 92%
“…[20] There are very few studies concerning the role and outcome of regional anesthesia in supine PCNL. [22] But in our best knowledge there is no data available in the literature regarding anesthetic outcome for supine totally tubeless/tubeless PCNL. Our study enlightens the role of regional anesthesia (spinal with epidural) in said procedures.…”
Section: Discussionmentioning
confidence: 99%
“…All PCNL procedures included in this meta-analysis were performed with patients in the prone position. While studies comparing prone to supine positions have demonstrated no significant difference in infection complications ( 28 - 30 ), this aspect should still be considered.…”
Section: Discussionmentioning
confidence: 97%